Phytol May Inspire New Medicinal Foods for the Treatment of Heart Disease - Pejin1, B.; Kartali2, T.; Stanimirovic3, B.; Karaman2, M. (Asian Journal of Chemistry, 2014)
This study aimed to investigate in vitro antibacterial activity of phytol against the selected Gram positive bacteria (Clostridium sporogenes, Enterococcus faecalis and Sarcina lutea) involved in the pathogenesis of infective endocarditis. The examined natural product has proved to be active against all the tested bacteria, but to a varying degree. Indeed, phytol inhibited E. faecalis growth (MIC 1.56 ± 0.04 μg/mL) more effectively than gentamycin and ampicillin (MIC 5.00 ± 0.06 and 16.00 ± 0.03 μg/mL, respectively). Both its freely presence in nutrition and easy availability support the development of a new phytol based medicinal foods targeting heart disease.